Analisis Sumber Daya Manusia, Desain Pekerjaan, dan Pengukuran Kinerja Karyawan Warung Roso - Rafika Amanda Dwi Amalia; Helmalia Fatimatus Zahra; Mila Ardani (CV. ITTC INDONESIA, 2026)
Human resources are one of the key factors in the success of a business, including those in the culinary sector. Effective employee management through task allocation, communication, and performance evaluation can help improve work effectiveness and service quality. This study aims to examine the implementation of human resource management, job design, and employee performance measurement at Warung Roso. The research employed a qualitative method, with data collected through direct interviews and observations. Based on the interview results, task allocation at Warung Roso is carried out according to operational needs, including production, customer service, and business management functions. The implemented job design helps employees understand their roles and responsibilities, enabling operational activities to run more systematically. In addition, employee performance is assessed based on discipline, responsibility, and service capability. Proper human resource management can support increased productivity and maintain the quality of business services.